Efficient direct conversion of lignocellulosic biomass into biobased platform chemicals in ionic liquid-water medium - Niş, Berna; Özsel Kaya, Burçak (Elsevier Ltd, 2021)
In this study, the conversion of corn straw, sorghum and cellulose into valuable chemicals (furfural, 5-hydroxymethylfurfural, levulinic acid) in different ionic liquid-water medium were investigated. Different reaction parameters such as reaction temperature, time and solvent ratio were optimized to achieve the highest conversion of biomass and selectivity of the products. Under the optimal reaction conditions (180 °C, 30 min, 1:5 ratio), 1-butyl-3-methylimidazolium hydrogen sulfate ([BMIM]HSO4) was found to display the highest efficiency which can be attributed to the acidic character of the ionic liquid. 117.4 mg levulinic acid, 11.8 mg 5-hydroxymethylfurfural and 9.4 mg furfural were obtained per g of sorghum. The results showed that 5-fold higher quantity of LA was obtained from sorghum biomass in comparison with pure cellulose. In addition, Amberlyst-15 was examined as a solid acid catalyst for conversion of cellulose in [BMIM]HSO4-water solvent system resulting in 4.6-fold increase in the quantity of levulinic acid. This study provides an alternative single step approach for production of valuable chemicals from renewable biomass.
Keywords: Hydroxymethylfurfural; Biomass conversion; Furfural; Ionic liquids; Levulinic acid